The Origin of Reality in Image - SASAKI, Kazuhiko (Annual review of sociology/ Nenpō shakaigaku ronshū, 2000)
This paper is a logical analysis of reality in images. I use the term “reality” to mean the force that compels us to repeatedly experience an image and at the same time attracts our visual desire. There are two purposes here: (1) to reveal the origin of “reality” in images, and (2) to consider what kind of desire could be generated by stimulating our sensibility. Regarding the concrete analysis, I first reveal characteristics of the human sense of sight. Secondly, I analyze the features of images and the human visual desire using Barthes's concept of “the gaze” and Lacan's concept of “objet petit a”. Finally, I present that the origin of “reality” in images consists in “the gaze” as “objet petit a”.